2012
DOI: 10.2147/opth.s29865
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endothelial cell loss and microcoaxial phacoemulsification parameters in noncomplicated cataract surgery

Abstract: PurposeTo assess the relationship between postoperative endothelial cell loss and microcoaxial phaco parameters using Ozil IP (Alcon Laboratories, Inc, Fort Worth, TX) in noncomplicated cataract surgery.MethodsIn this prospective observational study, 120 consecutive cases of cataract patients with different grades of nuclear hardness underwent microcoaxial phacoemulsification through a 2.2-mm clear corneal incision. An Alcon Infinity Vision System with Ozil IP (Alcon Laboratories) was used with an Ozil torsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 21 publications
1
56
0
1
Order By: Relevance
“…17 In contrast, Park et al 4 found that the ECC loss at 6 months was significantly higher in the microcoaxialincision group than in the standard-incision group (PZ.048). Mahdy et al 2 also found statistically significant endothelial cell loss with microcoaxial phacoemulsification, especially with increased nuclear hardness. With increasing cataract density, there was a need for more time and increased amounts of balanced salt solution to remove the lens.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…17 In contrast, Park et al 4 found that the ECC loss at 6 months was significantly higher in the microcoaxialincision group than in the standard-incision group (PZ.048). Mahdy et al 2 also found statistically significant endothelial cell loss with microcoaxial phacoemulsification, especially with increased nuclear hardness. With increasing cataract density, there was a need for more time and increased amounts of balanced salt solution to remove the lens.…”
Section: Discussionmentioning
confidence: 92%
“…This was associated with fluid turbulence in the anterior chamber and consequently more endothelial cell loss. 2 It is thought that corneal endothelial cells are more susceptible to damage with MICS than with standard-incision phacoemulsification, especially in eyes with hard cataract. We hypothesize that the phaco-chop technique may decrease the damage to corneal endothelial cells more than the stop-andchop and divide-and-conquer techniques, especially in microcoaxial phacoemulsification for hard cataract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] When the cornea is exposed to stresses such as dissipated phacoemulsification energy during cataract extraction, CECs may be damaged or permanently lost from the CEC monolayer. 6 The resultant discontinuity within the CEC monolayer is compensated by expansion and migration of neighboring healthy CECs in order to maintain its functional integrity. 7 When CEC density falls below a critical threshold of approximately 500 cells/mm 2 , the monolayer of CECs will no longer be able to exert sufficient homeostatic control to regulate corneal hydration.…”
mentioning
confidence: 99%
“…In healthy individuals, this natural reduction in endothelial cell density does not result in any clinically significant impairment in the structure and function of the cornea. However, accelerated and progressive endothelial cell losses, as experienced in pathological states such as Fuchs’ endothelial dystrophy (McCartney et al , ) and pseudophakic bullous keratopathy (Mahdy et al , ), are invariably accompanied by the clinical manifestations of corneal oedema and decreased visual acuity, with progression to irreversible corneal endothelial failure in some casess.…”
Section: Corneal Endothelial Cell Biologymentioning
confidence: 99%